Science and economic development : new patterns of living - Meier, Richard L. ([Cambridge] Technology Press of Massachusetts Institute of Technology, 1956)
This book traces out a new path for economic development which is suggested and shaped by postwar discoveries in sciences and technology.
Includes bibliographical references.
oif 13/02/2019
Loans
Keywords: Economic development; Economic history; Technology; Natural resources